2020
DOI: 10.1111/sms.13643
|View full text |Cite
|
Sign up to set email alerts
|

Endurance exercise training volume is not associated with progression of coronary artery calcification

Abstract: Background:Recent cross-sectional studies have suggested a dose-dependent relationship between lifelong exposure to physical activity and the burden of calcified coronary artery disease (CAD). No longitudinal studies have addressed this concern. Hypothesis: Exercise volume is associated with progression of coronary artery calcium (CAC), defined as ≥10 units increase in CAC score. Methods: Sixty-one recreational athletes who were assessed by coronary computed tomography angiography (CCTA) as part of the NEEDED … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Previous studies investigating coronary atherosclerosis in athletes are limited by their cross-sectional design and do not address the separate roles of exercise volume versus intensity because they either compare athletes with nonathletes 8,9 or do not examine intensity and volume separately. 10,20,21 We found that vigorous exercise lowered CAC progression, whereas very vigorous exercise accelerated it. Very vigorous exercise was also associated with increased progression of (calcified) plaque.…”
Section: Exercise Intensitymentioning
confidence: 73%
See 1 more Smart Citation
“…Previous studies investigating coronary atherosclerosis in athletes are limited by their cross-sectional design and do not address the separate roles of exercise volume versus intensity because they either compare athletes with nonathletes 8,9 or do not examine intensity and volume separately. 10,20,21 We found that vigorous exercise lowered CAC progression, whereas very vigorous exercise accelerated it. Very vigorous exercise was also associated with increased progression of (calcified) plaque.…”
Section: Exercise Intensitymentioning
confidence: 73%
“…Indeed, a study in 61 recreational athletes (74% male) found no significant difference in exercise volume between individuals with or without progression of CAC (68 [33 to 122] versus 50 [34 to 82] MET hours/week; P =0.16) after 4.1±0.3 years of follow-up. 20 In contrast, a Korean population study categorized 25 485 young (42±6 years) Korean men and women as inactive, moderately active, and health-enhancing physically active. Moderately active was defined as ≥3 days of vigorous intensity activity for ≥20 min/day, ≥5 days of moderate intensity activity for ≥30 min/day, or ≥5 days of activities attaining ≥600 MET min/week.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the late elevation of creatine kinase and myoglobin from skeletal muscle after high-load, long duration exercise is mirrored by the cTnT and cTnI elevations observed in young athletes [17] , [38] . Participants in extreme races often develop troponin elevations that are ten times the assay specific cutoff's that become more prominent after long bouts of exercise [39] and is related to duration of elevated heart rates [40] . Most studies have not excluded necrotic events, but necrosis is unlikely to be the only release mechanism as most participants that develop troponin elevations are young and fit.…”
Section: Discussionmentioning
confidence: 99%
“…Malik [121] reported continuous association between METs (Metabolic Equivalents of Task) and CAC-score, where at each 1 MET increase in exercise capacity results 66.2 AU lower CAC-score, however, for moderate intensity exercise (≤8.2 METs to < 10.6 METs) CAC-score remained similar with increasing minutes of exercise per week. Kleiven [122] demonstrated hours of endurance training per week had no association with progression of CAC, nevertheless correlated well with reported MET-h/week. Kermott [123] observed U-shaped distribution of CRF, which is defined by Functional Aerobic Capacity (FAC) measured in treadmill testing, on CAC-score across which those with FAC of 100% to 129% (Age:52.7 years, FRS:7.1, MET:12.2) had significantly lower CAC-score levels compared with FAC of ≤ 69% (Age:51.9 years, FRS:8.0, MET:7.2) and ≥ 130% (Age:55.4 years, FRS:8.2, MET:14.8) regardless of family history (FH) of CAD/premature CAD; however, those with highest CRF category of FAC ≥ 130% had lower level of LDL and Blood Glucose and higher level of HDL, moreover, in subgroup analysis of patients with ≥ 60 years of age adjusted with FH of CAD higher FAC categories associate with lower FRS, and consistently in initial overall-analysis participants grading FAC ≥ 130% had higher mean-age and rate of FH of premature CAD to a trend of higher FRS.…”
Section: Cac-development With Progressing Risk Factorsmentioning
confidence: 73%